Fractionation of kudzu amylose and amylopectin and their microstructure and physicochemical properties. (13th June 2016) - Wang, Zhanzhong; Chen, Boru; Zhang, Xiao; Li, Yan; Fang, Wenzhi; Yu, Xiaoting; Dang, Leping
Abstract : This study investigated the microstructure and physicochemical properties of amylose and amylopectin fractionated from kudzu starch. Enzymolysis of the fractionated amylose and amylopectin with pullulanase revealed significant differences in thed ‐glucose chain structures. The amylose molecule had a lower degree of polymerization (DPn ), with fewer but longer glucose unit chains compared with the amylopectin molecule. The average external and internal chain lengths of amylopectin were 12.71 and 7.21, respectively. X‐ray diffraction analysis of the crystalline structure of the starches showed that the amylopectin derived from kudzu starch was amorphous with no obvious diffraction pattern, whereas the amylose exhibited a superposition of the A and B type diffraction patterns, while the native starch exhibited typical C‐type patterns. The amylose fraction exhibited a higher iodine affinity and lower swelling power (SP) than the native starch, which was likely due to the water holding capacity of the hydrogen bonds within the starch molecules. The amylopectin had a very high solubility, a particular characteristic of kudzu starch which may render it suitable for certain special industrial applications. Analysis of the thermal properties of the starches revealed that amylose had a higher melting enthalpy than amylopectin, which may be related to the helical structure and higher crystallinity degree of this fraction. Collectively, these results are likely to inform future developments in the practical application of kudzu starch by industry, and enable improvements to be made in the functionality of products incorporating this starch.